Binding of copper (II) ion to cytochrome c - Augustin, Mary Ann; Yandell, John K. (CSIRO Publishing, 1981)
Binding of aquacopper(11) ion to horse and tuna ferricytochrome c has been investigated over the pH range 2-9. Between pH 4 and 7 the principal binding site for horse cytochrome has an intrinsic association constant of 1.8 × 104 1. mol-1 and pKa of 6.5±0.6 at 25ºC and ionic strength of 0.1. Binding to histidine 33 is consistent with this information, as well as with e.s.r., n.m.r. and visible absorption spectral data. Other sites also bind copper but with association constants at least a factor of ten smaller. At high pH (> 8) further binding sites predominate.